Feasibility of multianimal hyperpolarized 13C MRS. Issue 5 (5th June 2014) - Ramirez, Marc S.; Lee, Jaehyuk; Walker, Christopher M.; Chen, Yunyun; Kingsley, Charles V.; De La Cerda, Jorge; Maldonado, Kiersten L.; Lai, Stephen Y.; Bankson, James A.
Abstract : Purpose: There is great potential for real‐time investigation of metabolism with MRS and hyperpolarized (HP) 13 C agents. Unfortunately, HP technology has high associated costs and efficiency limitations that may constrain in vivo studies involving many animals. To improve the throughput of preclinical investigations, we evaluate the feasibility of performing HP MRS on multiple animals simultaneously. Methods: Simulations helped assess the viability of a dual‐coil strategy for spatially localized multivolume MRS. A dual‐mouse system was assembled and characterized with bench‐ and scanner‐based experiments. Enzyme phantoms mixed with HP [1‐ 13 C] pyruvate emulated real‐time metabolism and offered a controlled mechanism for evaluating system performance. Finally, a normal mouse and a mouse bearing a subcutaneous xenograft of colon cancer were simultaneously scanned in vivo using an agent containing HP [1‐ 13 C] pyruvate. Results: Geometric separation/rotation, active decoupling, and use of low input impedance preamplifiers permitted an encode‐by‐channel approach for spatially localized MRS. A precalibrated shim allowed straightforward metabolite differentiation in enzyme phantom and in vivo experiments at 7 Tesla, with performance similar to conventional acquisitions. Conclusion: The initial feasibility of multi‐animal HP 13 C MRS was established. Throughput scales with the number of simultaneously scanned animals, demonstrating the potential for significant improvements in study efficiency. Magn Reson Med 73:1726–1732, 2015. © 2014 Wiley Periodicals, Inc.